PENGEMBANGAN VIDEO PEMBELAJARAN INSTALASI LISTRIK PADA MATA KULIAH DASAR - DASAR INSTALASI LISTRIK DI PRODI PENDIDIKAN TEKNIK ELEKTRO UNDIKSHA - Angga Andiana Septian; Nyoman Santiyadnya; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2022)
This study aims to: 1) Make a video media for learning electrical installations in the electrical installation basics course, 2) know the feasibility of electrical installation learning video media in the electrical installation basics course, 3) and knowing the students’ responses to the electrical installation learning video media in the electrical installation basic course. This research includes the type of research R&D (Research and Development). This study uses statistical data analysis of the percentage of feasibility to process questionnaire data for content expert tests and media expert tests, while for small group tests and large group tests using Five Scale Standard model data analysis. The study used a questionnaire as a data collection instrument by content experts, media experts, and students. The results obtained: 1) the results of the media expert validation obtained a percentage of 88,5% with very decent qualifications, 2) the content expert validation results obtained a percentage of 88,09% with very decent qualifications, 3) the results of the small group trial were obtained from five respondents included in the very high category, 4) the results of the large group trial were obtained from twenty-five respondents all included in the very high category. Based on the results of the study, electrical installation learning video media is suitable for use in the learning process in the basics of electrical installation course in the Undiksha Electrical Engineering Education S1 Study Program.